Oxidative Cleavage of Indoles Mediated by Urea Hydrogen Peroxide or H2O2 in Polar Solvents. Issue 13 (4th June 2021) - Llopis, Natalia; Gisbert, Patricia; Baeza, Alejandro
Abstract: The oxidative cleavage of indoles (Witkop oxidation) involving the use of H2 O2 or urea hydrogen peroxide in combination with a polar solvent has been described. Among these solvents, 1, 1, 1, 3, 3, 3‐hexafluoroisopropanol (HFIP) stands out as the one affording the corresponding 2‐ketoacetanilides generally in higher yields The protocol described has also enabled the oxidation of different pyrroles and furans derivatives. Furthermore, the procedure was implemented in a larger‐scale and HFIP was distilled from the reaction mixture and reused (up to 4 cycles) without a significant detriment in the reaction outcome, which remarks its sustainability and applicability. Abstract :